1982
DOI: 10.1016/0167-4870(82)90010-1
|View full text |Cite
|
Sign up to set email alerts
|

Retail attribute sensitivity and shopping patronage

Abstract: Using conjoint analysis the sensitivity for the four most important retail attnbutes price, quality, assortment and locational convenience for food stores is measured for a sample of 400 consumers in Tilburg, The Netherlands In a second wave the actual shopping behavior is measured using a self-administrated questionnaire The sensitivity scores are used separately and m conjunction, as sensitivity patterns, to explain patterns of shopping behavior as well as separate shopping characteristics The relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 15 publications
(9 reference statements)
0
7
1
1
Order By: Relevance
“…Although few of these applications concerned retailing problems, some studies made retail applications of conjoint approaches (Ahn & Ghosh, 1989;Louviere & Gaeth, 1987;Louviere & Johnson, 1990Louviere & Meyer, 1981;Moore, 1990;Schuler, 1979;Timmermans, 1982;Timmermans, Borgers, & Van der Waerden, 1991;Timmermans, Van der Heijden, & Westerveld, 1982, 1984Verhallen & De Nooij, 1982). Moreover, almost all conjoint applications in retailing have studied preference or choice instead of perception of retail destination.…”
Section: Conjoint Retail Studies and Shopping Center Attributesmentioning
confidence: 99%
“…Although few of these applications concerned retailing problems, some studies made retail applications of conjoint approaches (Ahn & Ghosh, 1989;Louviere & Gaeth, 1987;Louviere & Johnson, 1990Louviere & Meyer, 1981;Moore, 1990;Schuler, 1979;Timmermans, 1982;Timmermans, Borgers, & Van der Waerden, 1991;Timmermans, Van der Heijden, & Westerveld, 1982, 1984Verhallen & De Nooij, 1982). Moreover, almost all conjoint applications in retailing have studied preference or choice instead of perception of retail destination.…”
Section: Conjoint Retail Studies and Shopping Center Attributesmentioning
confidence: 99%
“…Though consumer choice of shopping destination continues to be a research problem of considerable academic and applied interest, only a limited number of conjoint studies have focused on retail destination choice. They entail either consumer store choices (Louviere and Gaeth 1987;Louviere and Johnson 1991;Meyer and Eagle 1982;Moore 1990;Recker and Schuler 1981;Verhallen and De Nooij 1982) or shopping center choices (Timmermans 1982;Timmermans, Van der Heijden, and Westerveld 1984). Predictor variables typically were limited to small sets of broadly defined constructs, such as "selection," "prices," "atmosphere," and/or "distance."…”
Section: Analysis Of Integrated Hii Preference and Choicementioning
confidence: 98%
“…The factors that influence store choice and retail patronage have been subject to sustained scholarly interest for several decades (e.g. Arnold et al ., ; Arnold et al ., ; Arnold et al ., ; Darden and Lusch, ; Huff, ; James et al ., ; Lindquist, ; Monroe and Guiltinan, ; Pan and Zinkhan, ; Pessemier, ; Reilly, ; Tigert and Arnold, ; Verhallen and de Nooij, ). A review of the literature reveals that the most frequently reported antecedents to retail patronage are price, product selection or assortment and store location (Pan and Zinkhan, ).…”
Section: Store Choice In Retailmentioning
confidence: 99%